Perspectives on Barriers and Facilitators in Caring for Women with Gestational Diabetes in Rural Appalachia. Issue 5 (September 2019) - Chertok, Ilana R. Azulay; Silk, Jennifer J.; Kulasa, Kathryn A.
Abstract: Purpose: The purpose of this study was to explore perspectives of healthcare providers in rural Appalachia who care for pregnant women with gestational diabetes, including management facilitators and barriers. Study Design and Methods: Qualitative study with interviews and thematic analysis. Thematic analysis was conducted using the sort and sift method after inductive content analysis with open coding, identifying categories, and abstraction. Results: Twenty-one advanced practice nurses and 10 physicians participated in the study. Three themes were identified: rural healthcare challenges including limited resources and lack of adherence to recommendations, cultural influences including normalization of diabetes and food culture, and collaborative care including accessible resources and patient motivation. Clinical Implications: The themes provide insight into the perceived barriers and facilitators of healthcare providers caring for women with gestational diabetes in rural Appalachia. Consistent, evidence-based communication with cultural consideration supports effective education and care of women with gestational diabetes. Healthcare providers' knowledge of local resources, accessible electronic medical records, and communication among the various team members enhance collaboration in diabetic management in the rural setting. Abstract : In this study, nurses, midwives, and physicians caring for women with diabetes in rural Appalachia offered their thoughts on common challenges and factors that promoted best care. The main challenges included limited resources, lack of adherence to recommendations, cultural influences including normalization of diabetes, and food culture. Collaborative care including accessible resources and patient motivation were perceived as beneficial.